Hydrochemical characterization of the Ramsar-listed Koshi Tappu Wetland, Nepal - Neupane, Shristi; Pant, Ramesh Raj; Thapa, Lal B; Shah, Deep Narayan; Gautam, Birendra; Adhikari, Barsha; Khanal, Barsha; Acharya, Anueva; Bishwakarma, Kiran; Adhikari, Saroj (Journal of Nepal Chemical Society, 2023)
Nepal abounds a vast array of freshwater bodies, from sub-tropical lowlands to glacier-fed highlands with varying water quality. This study evaluated the spatial variations in water quality at the Koshi Tappu Wetland, the first Ramsar site of Nepal, located in the eastern Tarai region within the Koshi Tappu Wildlife Reserve. Nineteen water quality parameters were chosen and analyzed from twenty-one different sampling points within the wetland. Parameters including pH, EC, TDS, turbidity, and DO were analyzed on-site, whereas HCO3-, Cl-, NH4+, NO3-, SO42- PO43-, K+, TH, Ca2+, Mg2+, CaH, MgH, Na+, and Fe3+ were analyzed in the laboratory. Multivariate methods such as hierarchical agglomerative cluster analysis (CA) and principal component analysis (PCA), and geochemical indices such as piper and mixing diagrams were applied to assess the spatial variation in water quality. Findings indicated Ca2+ as the principal cation and HCO3- as the principal anion regulating the hydrochemistry of the wetland. Based on CA, three spatial clusters were observed, which depicted variations in chemical composition with the PCA results highlighting the primary contamination sources and controlling factors of the sampling locations with 84.13% of the total variance. Findings from the PCA and ionic relationship analyses elucidated that the hydrochemistry of the Koshi Tappu wetland is mainly controlled by carbonate weathering processes with a minor contribution of silicate weathering and anthropogenic activities.